Use of the internet by information professionals in some selected university libraries in South west, Nigeria (2009)
The Internet in Nigeria is a veritable tool to access information due to the poor economic situation and the non availability of current library materials. This study attempted to find out the level of use of the Internet and problems faced by information professionals. Thirty- two information professionals were selected from three university libraries in South West Nigeria and the questionnaire was used for data collection. The Internet was used mainly for Electronic mails and the main access point was through cybercafes. Slow Internet connection, cost of bandwidth and little knowledge of Internet facilities were the major problems highlighted.